2022
DOI: 10.1186/s12888-022-03725-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human library intervention on mental health literacy: a multigroup pretest–posttest study

Abstract: Background Mental health literacy (MHL) is an evolving concept encompassing knowledge of mental illness, help-seeking options, perceived stigma, and discrimination. This study aimed to test the effectiveness of a human library intervention at enhancing MHL. A human library intervention was adopted to enhance MHL in this study. The human library intervention aims to establish a positive framework and safe space for dialogue between readers and a ‘human book’. It works to promote dialogue, reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…One of the most recurring themes in defining the concept of MHL has been focused on knowledge/skills that enhance understanding (Chung & Tse, 2022; Gorczynski et al., 2020; Huang et al., 2019; Kutcher, Wei, & Coniglio, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most recurring themes in defining the concept of MHL has been focused on knowledge/skills that enhance understanding (Chung & Tse, 2022; Gorczynski et al., 2020; Huang et al., 2019; Kutcher, Wei, & Coniglio, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, on one hand, it is found that for an individual to be considered mentally health literate, they must have a good understanding of MDs (Chung & Tse, 2022; Gorczynski et al., 2020; Kutcher, Wei, & Coniglio, 2016; Kutcher, Wei, Gilberds, et al., 2016). It is important to note that not only should one consider disorders such as depression and anxiety, among others, but also understand those that are not as prevalent (Vimalanathan & Furnham, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of a living library to improve mental health outcomes has international appeal and has already been tried around the world in a range of contexts, including improving self-management strategies for people diagnosed with bipolar disorder, 16 reducing stigma in pharmacy students in Canada 17 ; and improving mental health literacy in students in Hong Kong. 18 Living books have reported a wide range of benefits including; a greater self-awareness, 19 personal enjoyment and enhanced social relationships, 20 21 catharsis from sharing experiences 22 and feeling valued in promoting change. 23 For readers, there is evidence for enhanced self-efficacy through discovering new ways to understand and manage specific difficulties.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These events are often held in open settings, including public and university libraries, and have typically aimed to challenge a range of societal prejudices by facilitating interactions between people who may not otherwise engage in conversation [15]. The model has also been used in a mental health context to address stigma [16] and facilitate peer-support [17]. However, implementation recommendations sensitive to the specific challenges of discussing mental health experiences are limited.…”
Section: Introductionmentioning
confidence: 99%